2016
DOI: 10.1177/2394901515627748
|View full text |Cite
|
Sign up to set email alerts
|

Financial Crisis, Exchange Rate Regimes, Organizational Forms, and Bank Efficiency: Does Globalization Matter?

Abstract: The article provides new empirical evidence on the impact of economic globalization on the efficiency of the banking sector. The analysis is confined into two stages. In the first stage, we employ the bias corrected data envelopment analysis method to compute the efficiency of individual banks during the period 1999-2008. We then use bootstrap regressions to examine the impact of economic globalization on bank efficiency, while controlling for the potential impacts of contextual variables. The empirical findin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 62 publications
(85 reference statements)
0
2
0
Order By: Relevance
“…Western culture has grown rapidly its effect on all facets of global life including growth in the economy. Majority of previous study suggested that CuGI had a favourable effect on productivity in the banking sector (Sufian et al , 2017; Sufian and Habibullah, 2014; Sufian, 2016).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Western culture has grown rapidly its effect on all facets of global life including growth in the economy. Majority of previous study suggested that CuGI had a favourable effect on productivity in the banking sector (Sufian et al , 2017; Sufian and Habibullah, 2014; Sufian, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…NIETA is used to measure the quality of bank administration and operations and can be defined as the ratio of non-interest expenses to the amount of total assets. Several studies such as Muda et al (2013) and Sufian (2016) confirm the adverse relationship between NIETA and performance. Notwithstanding, economic growth significantly and negatively affect bank productivity in Islamic banks.…”
Section: Globalisation On Bank Productivity In Seamentioning
confidence: 88%